Biochemical Study on Diabetic Nephropathy Patients - Ahmed, H. Sh.; -Ali, E. Abd; Abdullah, M. R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study deals with thirty non-insulin dependent diabetes mellitus patients suffering from diabetic nephropathy in addition to twenty five healthy control.Some biochemical parameters were determined in the serum of all subjects enrolled in the study.These parameters are serum glucose,serum urea,serum creatinine,total serum protein and serum albumin.The aim of the present study was to estimate these parameters in diabetic nephropathy  patients.     The results of the present study revealed a significant increase in glucose,urea and creatinine in patients as compared to controls . Also a significant decrease was found in total serum protein, serum albumin and albumin to globulin ratio (A/G) in patients compared to controls,while a significant increase in serum globulin in patients compared to control was found (P